2022
DOI: 10.4081/mrm.2022.822
|View full text |Cite
|
Sign up to set email alerts
|

Tracheostomy healing time after decannulation

Abstract: Background: Prolonged healing of tracheostomy after decannulation has a negative impact on respiration, hygiene, cosmetics, and social life. Even so, evidence-based observations of tracheostoma healing time are lacking. Therefore, the aim of this study was to determine tracheostomy wound healing time after decannulation.Methods: In this prospective observational cohort study, we included 30 subjects undergoing decannulation following prolonged mechanical ventilation via tracheostomy. Our primary endpoint was t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…V-Loc 90 barbed sutures were selected from among Quill barbed sutures made from polydioxanone, V-Loc 180 barbed sutures made from polyglycolic acid, and V-Loc 90 barbed sutures made from Glycomer 631. This is because V-Loc 90 with a 90-day absorption profile was the most appropriate, given that tracheal tissues heal for an average of 22 days (9). The size of the suture was determined according to the specimen size, with USP 3-0 V-Loc 90 being the most suitable.…”
Section: Discussionmentioning
confidence: 99%
“…V-Loc 90 barbed sutures were selected from among Quill barbed sutures made from polydioxanone, V-Loc 180 barbed sutures made from polyglycolic acid, and V-Loc 90 barbed sutures made from Glycomer 631. This is because V-Loc 90 with a 90-day absorption profile was the most appropriate, given that tracheal tissues heal for an average of 22 days (9). The size of the suture was determined according to the specimen size, with USP 3-0 V-Loc 90 being the most suitable.…”
Section: Discussionmentioning
confidence: 99%
“…1 It commonly happens after the removal of maxillary first and second molars, with incidence ranging from 0.31% to 4.7%. 2 In small and fresh OAC, simple suturing results in the closure of OAC. 3 In large defects and delayed closure, various…”
Section: The Use Of Titanium Meshes In Surgical Closure Of the Oroant...mentioning
confidence: 99%
“…Feng et al 1 reported a method that relied on the adhesive strength of the tape and obtained tracheostoma closure within 4.43 ± 0.57 days. Another study reported tracheostoma closure within 1 to 22 days (median: 6 d) after tracheal cannula removal 2 . In pediatric patients, the mean time to tracheostoma closure is reportedly 12 to 17 days (mean: 14 d) 3 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We read with great interest the article “Tracheostomy healing time after decannulation” by Christiansen et al [ 1 ]. The authors aimed to determine the tracheostomy wound healing time after decannulation.…”
mentioning
confidence: 99%